EFEKTIVITAS PAC (POLY ALUMINIUM CHLORIDE) DALAM MENURUNKAN KADAR FOSFAT PADA LIMBAH CAIR RUMAH SAKIT JIWA Prof. Dr. SOEROJO MAGELANG - Fitria Andriani; Yusniar Hanani Darundiati; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Level of phosphate in RSJ Prof. Dr. Soerojo Magelang’s waste water in 2016 still exceeded the quality standard according to Perda Jateng No. 5 of 2012 with average 3,63 mg/l. Advanced treatment processes to reduce phosphate can be done by chemical method that is coagulation flocculation with PAC (Poly Aluminum Chloride). This study aims to determine the effectiveness of PAC in reducing phosphate level of RSJ Prof. Dr. Soerojo Magelang’s waste water. This research is a true experimental research with the post test only control group design. Data analysis using One Way Anova. The population in this research is waste water generated by RSJ Prof. Dr. Soerojo Magelang and the sample consisted of 35 liters effluent of waste water. The results showed that phosphate level before treatment was 3.25 mg/l, control group was 2.99 mg/l, and addition of PAC dose as much as 0.3 gr; 0.4 gr; 0.5 gr; 0.6 gr; and 0.7 gr produced phosphate with value 1.83 mg/l; 1.48 mg/l; 1.43 mg/l; 1.34 mg/l; and 1.08 mg/l. Statistical analysis showed that there was a significant difference in reducing phosphate levels after the addition of PAC with dose 0,3 gr; 0,4 gr; 0,5 gr; 0,6 gr; and 0,7 gr. It can be concluded that PAC dose 0.3 gr is the most effective dose because can decrease phosphate in RSJ Dr. Soerojo Magelang’s waste water with effeciency of 43.69%.